COVID-19 Test Before Tokyo2020 Paralympic Games: An Implemented Protocol to Protect Paralympic Athletes - Muti, Greta E.; Muti-Schuenemann, Giovanna; Pimpinelli, Fulvia; Spataro, Antonio; Fiore, Antonio; Ciasullo, Francesca; Olivieri, Daniela; Rigoni, Marta; Delbue, Serena; Pariani, Elena; Muzi, Fabio; Donzelli, Sara; et al. (Frontiers in Sports and Active Living, 2022)
Objectives The COVID-19 pandemic represents a difficult challenge for the whole of humanity. Sports, in which contact between athletes is essential, became impossible to practice without the risk of viral spread. Athletes of the national teams are a particular subgroup of the population for whom there is an important need for protection and the implementation of targeted preventive measures. The present report describes the protocol that was developed to answer the urgent protection need for athletes during COVID-19 pandemic. The protocol aimed at demonstrating the feasibility of a rigid prevention intervention to prevent outbreaks and infections in terms of COVID-19 as well as in other potential future pandemics from pathogens with similar path of transmission. Methods The study was conducted in rowing para-thletes training of the Paralympic Games in Tokyo2020. It was designed to create an anti-COVID-19 “protection bubble” with the aim to isolate para-athletes and their technical support team during pre-Olympic retreats. The “bubble” development relied on a carefully conducted protocol of repeated antigen and molecular COVID-19 tests on nasal and oropharyngeal fluids among all participants carried out before, during and at the end of each retreat. Results During the 10 months of protocol implementation there were no COVID-19 outbreaks among the para-athletes and technical personnel during the retreats. In total, 552 PCR tests and 298 antigen-based tests were performed for an average number of 42 test per athlete. The number of retreat participants was larger (n = 23) in the beginning of the year due to the Paralympic selection rounds and smaller at the end of the study period (n = 12). Conclusion The protocol has indicated that it is possible to implement an anti-COVID-19 protection protocol where athletes and technical staff can train and compete in safe conditions. The study showed that it is feasible to implement a rigid prevention protocol for athletes and technical staff based on repeated COVID-19 antigenic and molecular tests for a long period of training with excellent participation and compliance.